Design of a new tensegrity cantilever structure. (1st July 2020) - Ma, Shuo; Chen, Muhao; Skelton, Robert E.
Abstract: This study mainly focuses on the design of a new cantilever structure and its minimal mass optimization subject to yield and buckling constraints. Given a vertical force in a constant distance from a vertical wall, the minimal mass design of a two elements structure with and without anchorage length limitation of the wall is first studied. To further reduce the total structural mass of, a sector cantilever structure is proposed, and the advantage of choosing equal bar length and connecting strings to the center of a circle is proved. Given finite anchorage length of the wall, a tailored sector cantilever structure with finite anchorage length is proposed. Minimal mass design of the sector cantilever with and without anchorage length constraint can be obtained by processing a constrained nonlinear optimization of shape parameters. Considering the penalty of joint mass, the optimal complexity of the sector cantilever will decrease as the penalty coefficient increases. Numerical results are given to show the efficiency of the proposed cantilever structures in saving mass.